2017
DOI: 10.1002/2016jc012420
|View full text |Cite
|
Sign up to set email alerts
|

Signature of mesoscale eddies in satellite sea surface salinity data

Abstract: A persistent signature of coherent mesoscale eddies in sea surface salinity (SSS) is revealed by analyzing the relationship between satellite SSS and sea surface height (SSH) variability in an eddy‐following reference frame. Our analysis focuses on mid‐ocean eddies in two representative regions, the southern Indian Ocean and the North Atlantic subtropical gyre. The resulting composite averages reveal a clear signature of mesoscale eddies in satellite SSS with typical SSS anomalies of 0.03–0.05 psu. The spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 33 publications
9
57
0
Order By: Relevance
“…Notable in this regard are the key contributions of the SSS data sets issued from the Soil Moisture and Ocean Salinity (SMOS; 2010 and ongoing), Aquarius (2011–2015), and Soil Moisture Active Passive (2015 and ongoing) satellite missions (Kerr et al, ; Lagerloef et al, ; Reul et al, ; Tang et al, ). Based on these satellite data sets, the signature of mesoscale variability and eddies on SSS has been documented in various regions, in particular, in the North Atlantic subtropical gyre, in the Gulf Stream region, in the Gulf of Mexico, in the Bay of Bengal, in the southern Indian Ocean, and in line with the occurrence of tropical instability waves in the Atlantic and Pacific Oceans (Fournier et al, , ; Kolodziejczyk et al, ; Lee et al, , ; Melnichenko et al, ; Reul et al, ; Yin et al, ). Despite these few studies, little is known about the eddy‐induced SSS changes, especially in tropical regions where the influence of mesoscale eddies on SSS remain poorly documented in the literature compared to the influence of the large‐scale circulation, climate modes, and long‐term trends.…”
Section: Introductionmentioning
confidence: 99%
“…Notable in this regard are the key contributions of the SSS data sets issued from the Soil Moisture and Ocean Salinity (SMOS; 2010 and ongoing), Aquarius (2011–2015), and Soil Moisture Active Passive (2015 and ongoing) satellite missions (Kerr et al, ; Lagerloef et al, ; Reul et al, ; Tang et al, ). Based on these satellite data sets, the signature of mesoscale variability and eddies on SSS has been documented in various regions, in particular, in the North Atlantic subtropical gyre, in the Gulf Stream region, in the Gulf of Mexico, in the Bay of Bengal, in the southern Indian Ocean, and in line with the occurrence of tropical instability waves in the Atlantic and Pacific Oceans (Fournier et al, , ; Kolodziejczyk et al, ; Lee et al, , ; Melnichenko et al, ; Reul et al, ; Yin et al, ). Despite these few studies, little is known about the eddy‐induced SSS changes, especially in tropical regions where the influence of mesoscale eddies on SSS remain poorly documented in the literature compared to the influence of the large‐scale circulation, climate modes, and long‐term trends.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite missions have revealed that SSS anomalies associated with eddies can be monitored for months near river outflows (Fournier, Vandemark, et al, ; Fournier, Vialard, et al, ) and large anomalies can be seen in the tropical Pacific Ocean following El Niño and La Niña events (Hasson et al, , ). Studies have also shown that remotely sensed SSS in the tropical Pacific Ocean be used to trace mesoscale features such as tropical instability waves (Lee et al, ; Melnichenko et al, ; Yin et al, ) and heavy rainfall associated with large convective cells in the ITCZ (Supply et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some research reveals the SSS signals that were not captured by the in situ data. For example, Aquarius SSS data captures many fine scale ocean structures, including the salinity fronts in the tropical Pacific [3], tropical instability waves in both the Pacific and Atlantic [4], the haline wake over the Amazon plume after the passage of hurricanes [5], and salinity anomalies and fluxes associated with the ocean eddy field [6].…”
Section: Introductionmentioning
confidence: 99%